Típicos divergentes: entre a sala de aula, a sala de recursos multifuncionais e o Movimento da Neurodiversidade - MATOS, Wlisses Figueiredo (2024)
This study corresponds to an exploratory, descriptive research with a qualitative approach, starting with an analysis of the discourses of the neurodiversity social movement, a movement led by neurodivergent people, who describe themselves as having atypical neurological connections, and demand that this singularity be treated as an issue of human difference, within the multiplicity of distinctions that characterize humans (sexual, gender, ethnic, racial, among others), from the perspective of authors such as Judy Singer (1999, 2017) Tiago Abreu (2021), Lorna Wing (1981) , Francisco Ortega (2008, 2009), among others. With theoretical bases from feminism and other movements, with quotes from Judith Butler (2003, 2004), Joan Scott (1998), Carla Akotirene (2019), Simone Beauvoir (1980), etc. The actors also criticize the overvaluation of the diagnosis, sometimes ableist, in the educational practices of Specialized Educational Services - AEE, instigating the problem of this research: Is it viable to apply the discourse of the Neurodiversity Movement in the schooling experiences of neurodivergent children? This research was carried out with 9 AEE teachers from the multifunctional resource rooms of 5 Basic Education Units (UEB's) in the Itaqui Bacanga area, on the outskirts of São Luís. Thus, this study analyzed the data collected through a semi-structured script of interviews, as a primary objective, the feasibility of applying the discourse of the Neurodiversity Movement in the schooling experiences of neurodivergent children in these UEB's, demonstrated in many statements by the teachers researched. The secondary objectives corresponded to the investigation of the clinician's speech pattern and its interference in the production of teaching methodologies used in regular classrooms and Multifunctional Resource Rooms (SRM), observed with great recurrence given that the diagnosis is a basic requirement in enrollment and in methodologies applied in the school process of these students; the identification of the principles that guide the theoretical formulations of the Neurodiversity Movement and the existence/non-existence of influences on the processes elaborated and/or practiced by the AEE, were perceived but indirectly given that the teachers do not know about the movement, but highly value individuality of neurodivergent students. Some of these observed results open up space for projects to raise awareness in the school environment to spread the movement, given the relevance for the training of teachers working in AEE in public schools with knowledge that helps them understand the complexity of the demands that exist in the inclusive perspective of education. special, opening ways to build and implement methodologies that are evidently inclusive and less ableist for the education of these children.